Improving Language Proficiency in Writing Descriptive Texts Among Seventh Grade Students of SMP Negeri 2 Gorontalo - Sanasia - (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to improve students’ language proficiency in the aspect of writing descriptive texts among seventh-grade students at SMP Negeri 2 Gorontalo through the implementation of innovative and student-centered learning strategies. The problems identified in writing instruction include students’ low ability to generate ideas, develop concepts, use descriptive vocabulary, and organize text structures coherently. This study is based on theories of writing skills, the process approach, constructivism, and contextual learning. The implementation of learning strategies was carried out through the use of visual media, direct observation activities, outlining exercises, as well as revision and peer feedback activities. The results of the implementation showed an improvement in students’ ability to write descriptive texts. Students became more active, creative, and capable of producing more detailed, systematic, and well-structured descriptive texts. In addition, the use of visual media and collaborative learning was proven to increase students’ motivation and self-confidence in writing. Therefore, the application of contextual, systematic, and process-based learning strategies has proven effective in improving students’ language proficiency, particularly in writing descriptive texts.